Sharia Contract Implementation after Institutional Transformation: BTN Syariah and BSN - Nabila Adenina Zidni Maulida; Ahmad Nur Habibi; Ghufron Ainul Yakin; Fida Rif'atul Khasanah (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2026)
The transformation of Islamic banking institutions through the spin-off policy has become a strategic effort to strengthen governance, operational independence, and sharia compliance in Indonesia’s Islamic banking industry. However, studies examining the impact of institutional transformation on the implementation of sharia contracts remain limited. This study aims to analyze the implementation of mudharabah and wadiah contracts before and after the transformation of BTN Syariah into Bank Syariah Nasional (BSN). Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving bank employees, sharia supervisory personnel, and customers. The findings indicate that the transformation did not change the substantive principles of mudharabah and wadiah contracts, but significantly improved their operational implementation through stronger governance, enhanced risk management, standardized procedures, greater transparency, and stricter sharia supervision. Furthermore, the transformation strengthened sharia compliance and good corporate governance, contributing to greater professionalism and customer trust in Islamic banking institutions.